District-level analysis of socio-demographic factors and COVID-19 infections in Greater Accra and Ashanti regions, Ghana - Owusu, Alex Barimah; Yiran, Gerald Albert Baeribameng; Afagbedzi, Seth K.; Takyi, Edwin (Frontiers in Public Health, 2023)
ABSTRACT Since December 2019 when COVID-19 was detected, it took the world by surprise in terms of spread and morbidity/mortality. The high rate of spread and casualties recorded from COVID-19 called for research in all directions to find ways to contain and reverse the incidences. It is against this background that this paper sought to measure the association of the socio-demographic factors in the hard-hit districts in Greater Accra and Ashanti to analyze its relationship with the novel COVID-19 virus. Data on COVID-19 cases from 35 Districts in both Greater Accra and Ashanti Regions were collected from the Ghana Health Service and population data from Ghana Statistical Service. Descriptive statistics and regression analysis were generated using R . We found that some socio-demographic variables have an association with COVID-19 infections. For example, age and religion especially Christianity and Islam pose risk to COVID-19. The population aged 15 to 64 was also at high risk of infections due to the high level of movement of this age group. We, therefore, recommend that places of congregation such as Churches and Mosques be targeted for vigorous sensitization on COVID-19 protocols and prevention. Also, districts with a high population between the age of 15 to 64 should step sensitization efforts to educate their inhabitants on the need to reduce travel and related activities in order to curb the spread of the virus.